Pregabalin Does Not Affect Sperm Production in Healthy Volunteers: A Randomized, Double‐blind, Placebo‐controlled, Noninferiority Study. Issue 2 (23rd January 2014) - Sikka, Suresh C.; Chen, Crystal; Almas, Mary; Dula, Eugene; Knapp, Lloyd E.; Hellstrom, Wayne J.G.
Abstract Objective The primary objective of this study was to compare the effects of pregabalin and placebo on sperm concentration in healthy male subjects. Changes in follicle‐stimulating hormone (FSH), testosterone, sperm motility, semen volume, and sperm morphology were also examined. Methods This was a phase 4, multicenter, double‐blind, randomized, placebo‐controlled, noninferiority study. A 12‐week treatment period (placebo or 600 mg/day of pregabalin) was followed by a 1‐week taper period and a 13‐week washout period. The primary outcome measure was the percentage of subjects with a ≥ 50% reduction from baseline in sperm concentration at End of Study. Results One hundred and nine subjects received placebo and 111 subjects received pregabalin. The difference between placebo and pregabalin with respect to the percentage of subjects with a ≥ 50% reduction from baseline in sperm concentration at End of Study was 6% (95% CI: −2.29 to 14.3%). Noninferiority of pregabalin compared to placebo was declared as the upper bound of the 95% CI was less than the prespecified noninferiority margin of 20%. There were no significant differences between placebo and pregabalin groups with respect to their effects on FSH, testosterone, or sperm motility. Changes in semen volume and sperm morphology were numerically similar in both treatment groups. Adverse events were consistent with the known safety profile of pregabalin. Treatment with 600 mg/day pregabalin for 12 weeks does not adversely affect spermatogenesis or serum levels of FSH and testosterone in healthy males.